The Bright Continent African Art History - Curnow, Kathy (Open textbook library., 2018)
This book aims to act as your map through the world of African art. As such, it will help you define the competencies you need to develop–visual analysis, research, noting what information is critical, asking questions, and writing down your observations–and provide opportunities for you to practice these skills until you are proficient. It will also expose you to new art forms and the worlds that produced them, enriching your understanding and appreciation. This is an ongoing project. Your text will not be complete the day you first click on it, but will be written as we proceed through the course. Because it will be used for other courses beyond your own, you may find that it includes materials beyond those your class demands. Encourage your curiosity–chase after it.